Characteristics of Ice Cream With the Addition of Nutmeg Puree (Myristica fragrans Houtt). - Sitti N A Soulisa; La Ega; Gelora H Augustyn (Universitas Pattimura, 2023)
Ice cream is one of the frozen processed products with milk-based ingredients and has various flavors, colors, and soft textures, so many enthusiasts are among the public, from children to adults. Ice cream flour is flour that is processed from various milk mixtures. This study aims to determine the appropriate concentration of nutmeg puree on the characteristics of ice cream. The experimental design used was a completely randomized design consisting of one factor, namely the addition of nutmeg puree with four treatment levels, as follows: (P0) Control without adding nutmeg puree, (P1) 50 g of nutmeg puree or 4.9%, (P2) 100 g nutmeg puree or 9.8% (P3) 150 g nutmeg puree or 14.7%. Based on the results of the study, it can be concluded that the treatment of adding 100% nutmeg puree was the best result with a total dissolved solids value of 22.57%, vitamin C 0.03%, the fat content of 1.51% and chemical-physical tests in the form of overrun and melting rate respectively 51.38% and 15.74 minutes. Based on organoleptic tests, including color, taste, aroma, and texture, adding 100% nutmeg puree gave a liking value.